Structural and Antimicrobial Studies of Some Macrocyclic Complexes of Copper(II) of Bioinorganic Relevance - Ambwani, Jitendra (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes have been synthesized by condensing thiodiacetic acid dihydrazide with 2,6-diacetylpyridine2,6- pyridinedicarbonyldichloride in presence of copper(II) ions. The complexes have the formulae Cu[DPTDH](BF4)2 and Cu[DCTDH](BF4)2 (where DPTDH = 2,6-diacetylpyridine-N-thiodiacetoylhydrazone and DCTDH = 2,6-pyridinedicarbonyl-dichloride- N-thiodiacetoylhydrazone). The synthesized complexes have been characterized by elemental studies, conductivity measurements, and spectral (IR and electronic) studies. All these complexes have been tested in vitro for their antimicrobial activity against bacteria Staphylococcus arueus (gram positive) and Escherichia coli (gram negative) and fungi Candida albicans and Aspergillus niger.